2004
DOI: 10.1094/pdis.2004.88.8.878
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Concentrations of Sphaerotheca macularis Conidia in the Air, Environmental Conditions, and the Incidence of Powdery Mildew in Strawberry

Abstract: Atmospheric concentrations of Sphaerotheca macularis conidia were monitored for 2 years on a strawberry crop in Huelva (southwestern Spain). The presence of airborne conidia was determined to assess the role of weather conditions on conidial release. The relationship between airborne conidia and incidence of powdery mildew on fruit was also studied. Concentrations of conidia were estimated with a Burkard volumetric spore sampler. The presence of conidia was related to temperature, relative humidity, and rainfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 11 publications
1
24
1
1
Order By: Relevance
“…Under our conditions (i.e., in protected systems, with no rainfall), wind is assumed to be the main factor for spore dispersal. This is in agreement with previous reports that showed the a daily cyclical pattern of spore dispersal in strawberry powdery mildew, with highest spore concentrations in the air measured between 12:00 and 16:00 (Peries 1962;Blanco et al 2004) and with many results indicating the importance of wind for spore dispersal in powdery mildews (Yarwood 1957;Butt 1978). Another mechanism of spore dispersal may be the passing of harvesters, which may provide an efficient way to spread the disease, especially where two manual handpickings per week can be made during production peaks.…”
Section: Discussionsupporting
confidence: 93%
“…Under our conditions (i.e., in protected systems, with no rainfall), wind is assumed to be the main factor for spore dispersal. This is in agreement with previous reports that showed the a daily cyclical pattern of spore dispersal in strawberry powdery mildew, with highest spore concentrations in the air measured between 12:00 and 16:00 (Peries 1962;Blanco et al 2004) and with many results indicating the importance of wind for spore dispersal in powdery mildews (Yarwood 1957;Butt 1978). Another mechanism of spore dispersal may be the passing of harvesters, which may provide an efficient way to spread the disease, especially where two manual handpickings per week can be made during production peaks.…”
Section: Discussionsupporting
confidence: 93%
“…Sivapalan (1993) demonstrated that rain can cause physical damage to mildews, and the correlation between rainfall and strawberry powdery mildew conidia was negative and significant (Blanco et al 2004). However, in our study, only 4 rainy days occurred in the 2007-2008 season when spores were trapped.…”
Section: Discussioncontrasting
confidence: 56%
“…Smith and Davies (1973) studied relationships between weather conditions and spore trap catches of barley mildew. The effect of meteorological factors on dispersal of other powdery mildew conidia such as apple powdery mildew (Sutton and Jones 1979;Xu et al 1995), grape powdery mildew (Willocquet and Clerjeau 1998), cherry powdery mildew (Grove 1998) and strawberry powdery mildew (Blanco et al 2004) have been studied. However, there are few studies on the relations between conidial dispersal and powdery mildew in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…In spring, at the time of regrowth on June-bearing cultivars, the disease can be initiated by ascospores produced in cleistothecia or by conidia produced on mycelia that survived the winter ( 12). Secondary cycles are initiated by conidia produced on P. aphanis colonies and are responsible for disease progress during the growing season (3).…”
mentioning
confidence: 99%
“…Knowledge of spatial and temporal structure of an epidemic is crucial for the development of sound sampling strategies. Such information is not available for strawberry powdery mildew (3,4,6).…”
mentioning
confidence: 99%